2003
DOI: 10.1046/j.1365-2699.2003.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in spectral reflectance among populations of Dendrobates pumilio, the strawberry poison frog, in the Bocas del Toro Archipelago, Panama

Abstract: Aim  The goal of this study was to quantify levels of variation in spectral reflectance within and among populations of Dendrobates pumilio, the strawberry poison frog from the Bocas del Toro Archipelago. Location  This study was carried out in the Bocas del Toro Archipelago, in the Republic of Panama, Central America. Methods  Spectral reflectance was measured for samples of individuals from fifteen distinct island and mainland populations, using an Ocean Optics 2000 spectrometer and a BiLink portable compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 41 publications
4
122
0
3
Order By: Relevance
“…We were also able to visually compare the general shape of our reflectance curves to those reported in Summers et al (2003). Previous studies found that O. pumilio (Schmidt) do not reflect UV light (Summers et al 2003). Therefore, we verified that our clay mixtures and permanent marker used to create eyes did not reflect UV light.…”
Section: Methodssupporting
confidence: 68%
See 3 more Smart Citations
“…We were also able to visually compare the general shape of our reflectance curves to those reported in Summers et al (2003). Previous studies found that O. pumilio (Schmidt) do not reflect UV light (Summers et al 2003). Therefore, we verified that our clay mixtures and permanent marker used to create eyes did not reflect UV light.…”
Section: Methodssupporting
confidence: 68%
“…We measured the color directly from the color chart, compared it with each clay mixture, and adjusted the mixtures accordingly. We were also able to visually compare the general shape of our reflectance curves to those reported in Summers et al (2003). Previous studies found that O. pumilio (Schmidt) do not reflect UV light (Summers et al 2003).…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, Dolenská et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%